54. Best practices in synchronous conferencing moderation - Anderson, Lynn; Fyvie, Barb; Koritko, Brenda; McCarthy, Kathy; Murillo Paz, Sonia; Rizzuto, Mary; Tremblay, Remi; Sawyers, Urel (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2006)
Practical guidelines are offered for the use of online synchronous conferencing software by session administrators and moderators. The configuration of the software prior to conferencing sessions is discussed, and the planning and implementation of useful collaborative activities such as "synchronised browsing". The combination of these practices into useful "patterns" for specific online conferencing purposes is discussed.